Exploring New Findings on Amyloidosis - Fernandez-Escamilla, Ana-Maria (IntechOpen, 2016)
Amyloid protein aggregates are involved in ''protein-misfolding diseases'' of enormous social and economic impact, still with no effective therapies. The most prevalent amyloid pathologies are related to neurodegenerative diseases, but amyloidosis also affects other organs. The majority of the studies includes serious health connotations on amyloids. However, not all amyloid fibers play a detrimental role in host. An increasing number of studies shows an important beneficial role as ''functional amyloids''. This book opens an exciting door to provide up-to-date information about the function and the mechanisms of the amyloid formation process from the structural, biophysical, biomedical, and nanotechnological perspective, combining the new findings on toxic and functional amyloids studies using theoretical and experimental approaches to fight against amyloid-based diseases.